A comprehensive laboratory‐based program for classification of variants of uncertain significance in hereditary cancer genes. (20th December 2013) - Eggington, J.M.; Bowles, K.R.; Moyes, K.; Manley, S.; Esterling, L.; Sizemore, S.; Rosenthal, E.; Theisen, A.; Saam, J.; Arnell, C.; Pruss, D.; Bennett, J.; et al.
<x xml:space="preserve">Abstract</x> Genetic testing has the potential to guide the prevention and treatment of disease in a variety of settings, and recent technical advances have greatly increased our ability to acquire large amounts of genetic data. The interpretation of this data remains challenging, as the clinical significance of genetic variation detected in the laboratory is not always clear. Although regulatory agencies and professional societies provide some guidance regarding the classification, reporting, and long‐term follow‐up of variants, few protocols for the implementation of these guidelines have been described. Because the primary aim of clinical testing is to provide results to inform medical management, a variant classification program that offers timely, accurate, confident and cost‐effective interpretation of variants should be an integral component of the laboratory process. Here we describe the components of our laboratory's current variant classification program (VCP), based on 20 years of experience and over one million samples tested, using the BRCA1/2 genes as a model. Our VCP has lowered the percentage of tests in which one or more BRCA1/2 variants of uncertain significance (VUSs) are detected to 2.1% in the absence of a pathogenic mutation, demonstrating how the coordinated application of resources toward classification and reclassification significantly impacts the clinical utility of testing.